Coral reefs of the Eastern Tropical Pacific : persistence and loss in a dynamic environment - Glynn, Peter W., 1933-; Manzello, Derek P.; Enochs, Ian C. (Springer, 2016)
This book documents and examines the state of health of coral reefs in the eastern tropical Pacific region. It touches on the occurrence of coral reefs in the waters of surrounding countries, and it explores their biogeography, biodiversity and condition relative to the El Niño southern oscillation and human impacts. Additionally contained within is a field that presents information on many of the species presented in the preceding chapters.
Keywords: Coral reefs and islands -- Pacific Ocean.; Pacific Ocean.; elektronické knihy; electronic books